Catalytic oxidative chemical treatment for the removal of elemental mercury on carbon steel (SAE J429) surface - Farah Ilyana Khairuddin, 1987-; Wan Azelee Wan Abu Bakar; Rusmidah Ali; Abdul Aziz Abdul Kadir; Fakulti Sains (2012)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2012